Electrification as development for sustainable livelihoods at Mt. Kasigau, Kenya. Issue 4 (2nd October 2019) - Myers, Christopher W.; Medley, Kimberly E.
Abstract: Kenya's Vision 2030 is expanding the electric grid as a national development initiative. We examine its introduction since 2009 to three rural villages at Mt. Kasigau, using participatory GIS (PGIS) to map the infrastructural development process and semi-structured interviews to gain local perspectives on community and household-level effects . The study mapped eight transformers, 164 connections and 11, 607 m of power lines, servicing 18% of the settled land area and 38–71% of village populations. Respondents highlight distinctions among availability, accessibility, and reliability for homes and in their communities but emphasize positive contributions to diverse capabilities and local livelihoods from this intervention.